Gifting representations’ analysis in the digital environment of Moscow museums - V. D. Romanov (Цифровая социология)
The article presents the research results of gifting online-representations of 170 museums in Moscow (federal, regional, private). Data collection and its interpretation were structured around the duality of the museum gift as a semantic unit representing the following categories: 1) appeals and requests from museums for different types of property support (new items or monetary donations); 2) gifts previously given to the museum, presented in electronic catalogues. The data collected from the materials of Moscow museums’ websites showed that appeals for assistance to museums, regardless of the type of charity, are the lot of a minority (8–15 %). In turn, 82 museums have systematized electronic catalogues, among them only 13 % clearly distinguish information about the way of items’ arrival and through a gift, including in a separate category of description. Considering a long history of philanthropists’ influence on the formation and development of museums, and evidence of existing museum support practices, the author does not argue about low intensity of donations in museum institutions, but offers to draw a conclusion about the relationship between low articulation of gift intentions and donations in the collections and functioning of the museum field in Moscow, its rules and shared norms.